2022
DOI: 10.1002/jlb.3a0821-451rr
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte-derived extracellular vesicles aggravate inflammation by promoting the proinflammatory macrophage phenotype through TLR4–MyD88–NF-κB–MAPK pathway

Abstract: Transfusion of stored erythrocytes is associated with the increased risk of morbidity and mortality in critical infections, but the mechanism is incompletely understood. Previous studies have suggested that RBC‐derived extracellular vesicles (EVs) may be potential risk factors for the occurrence of transfusion‐related immunomodulation. The purpose of our study was to evaluate the effects of RBC‐derived EVs under inflammatory conditions and explore the underlying mechanisms. In vivo, the activity of EVs was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Proinflammatory cytokines, including TNFα, IL‐1β, and IL‐6, that are generated in macrophages are key mediators of inflammation and immunity 24,25 . As indicated by ELISA results illustrated in Figure 2, the generation of proinflammatory cytokines was significantly induced by BisGMA at 3 μM ( p < .05).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Proinflammatory cytokines, including TNFα, IL‐1β, and IL‐6, that are generated in macrophages are key mediators of inflammation and immunity 24,25 . As indicated by ELISA results illustrated in Figure 2, the generation of proinflammatory cytokines was significantly induced by BisGMA at 3 μM ( p < .05).…”
Section: Resultsmentioning
confidence: 89%
“…The content of proinflammatory cytokines, such as TNFα, IL-1β, and IL-6, was considerably elevated in the activated macrophages under inflammatory conditions. 24,25 The expression of the proinflammatory cytokines was attenuated by wogonin in the RAW26.7 macrophages cotreated with LPS, ethanol, double-stranded RNA, and the serum of mice cotreated with streptozotocin. 4,5,37 The upregulation of TNF-α, IL-1β, and IL-6 in the macrophages was induced by BisGMA.…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocyte-derived EVs may amplify inflammation through thrombin-dependent complement activation ( Zecher et al., 2014 ; Almizraq et al., 2016 ; Fischer et al., 2017 ). In vitro , erythrocyte-derived EVs induced the M1 polarization of macrophages and increased the release of pro-inflammatory cytokines, the underlying mechanism may be EVs-mediated upregulation of TLR4-MyD88-NF-κB-MAPK activity ( Gao et al., 2022 ).…”
Section: Role Of Evs In the Pathogenesis Of Sepsismentioning
confidence: 99%
“…Transfusion of red blood cell suspensions is an important treatment for critically ill patients, but it has been found that it may aggravate the inflammatory response in sepsis ( Wu et al., 2017 ). This pro-inflammatory response may be associated with EVs from stored erythrocytes ( Straat et al., 2016 ; Gao et al., 2022 ). Erythrocyte-derived EVs may amplify inflammation through thrombin-dependent complement activation ( Zecher et al., 2014 ; Almizraq et al., 2016 ; Fischer et al., 2017 ).…”
Section: Role Of Evs In the Pathogenesis Of Sepsismentioning
confidence: 99%
“…Transfusion Related Immune Modulation (TRIM) might be also associated with sRMVs through interactions with cells that change the cytokine secretome profile or the survival dynamics of peripheral blood mononuclear cells [ 191 ]. The immunomodulatory effects of sRMVs are actually confirmed by the production of pro-inflammatory cytokines by bone marrow-derived macrophages in vitro, probably constituting a risk factor for transfusion related- adverse effects [ 192 ]. sRMVs accumulation in the presence of neutrophils triggers ROS production, suggesting another mechanism towards the induction or promotion of transfusion-related acute lung injury (TRALI) [ 193 ].…”
Section: Red Blood Cell Vesiculationmentioning
confidence: 99%